The Polyamine Putrescine Contributes to H2O2 and RbohD/F-Dependent Positive Feedback Loop in Arabidopsis PAMP-Triggered Immunity - Liu, Changxin; Atanasov, Kostadin E.; Tiburcio, Antonio F.; Alcázar, Rubén (Frontiers in Plant Science, 2019)
Polyamines are involved in defense against pathogenic microorganisms in plants. However, the role of the polyamine putrescine (Put) during plant defense has remained elusive. In this work, we studied the implication of polyamines during pathogen-associated molecular pattern (PAMP)-triggered immunity (PTI) in the model species Arabidopsis thaliana. Our data indicate that polyamines, particularly Put, accumulate in response to non-pathogenic Pseudomonas syringae pv. tomato DC3000 hrcC and in response to the purified PAMP flagellin22. Exogenously supplied Put to Arabidopsis seedlings induces defense responses compatible with PTI activation, such as callose deposition and transcriptional up-regulation of several PTI marker genes. Consistent with this, we show that Put primes for resistance against pathogenic bacteria. Through chemical and genetic approaches, we find that PTI-related transcriptional responses induced by Put are hydrogen peroxide and NADPH oxidase (RBOHD and RBOHF) dependent, thus suggesting that apoplastic ROS mediates Put signaling. Overall, our data indicate that Put amplifies PTI responses through ROS production, leading to enhanced disease resistance against bacterial pathogens.